Effects of the Elevation Training Mask® 2.0 on dyspnea and respiratory muscle mechanics, electromyography, and fatigue during exhaustive cycling in healthy humans - Boyle, K. G.; Napoleone, G.; Ramsook, A. H.; Mitchell, R. A.; Guenette, J. A. (Journal of Science and Medicine in Sport, 2022)
Objectives. Examine the effects of the Elevation Training Mask® 2.0 (ETM) on dyspnea, and respiratory muscle function and fatigue during exercise. Design. Randomized crossover. Methods. 10 healthy participants completed 2 time-to-exhaustion (TTE) cycling tests while wearing the ETM or under a sham control condition. During the sham, participants were told they were breathing air equivalent to "9000 ft" (matched to the selected resistance valves on the ETM according to the manufacturer), but they were breathing room air. Dyspnea and leg discomfort were assessed using the modified 0-10 category-ratio Borg scale. Qualitative dyspnea descriptors at peak exercise were selected from a list of 15. Crural diaphragmatic electromyography (EMGdi) and transdiaphragmatic pressure (Pdi) were measured via a multipair esophageal electrode balloon catheter. Participants performed maximal respiratory maneuvers before and after exercise to estimate the degree of respiratory muscle fatigue. Results. Exercise with the ETM resulted in a significant decrease in TTE (p = 0.015), as well as increased dyspnea at baseline (p = 0.032) and during the highest equivalent submaximal exercise time (p = 0.0001). The increase in dyspnea with the ETM was significantly correlated with the decrease in exercise time (r = 0.73, p = 0.020). EMGdi and Pdi were significantly increased with the ETM at all time points (all p < 0.05). There was a significant increase in the selection frequency of "my breath does not go in all the way" at peak exercise with the ETM (p = 0.02). The ETM did not induce respiratory muscle fatigue. Conclusions. Exercising with the ETM appears to decrease exercise performance, in part, by increasing the sensation of dyspnea.